Peirce’s presence in recent psychoanalytic literature: in what directions? - Guimarães Filho, Paulo Duarte (2017)
This article highlights how elements of Peirce’s philosophy have been used in recent psychoanalytic literature. Some papers from distinguished authors in this area are considered, showing how they try to have contributions from Peircean conceptions to clarify psychoanalytic matters. The subject of one of the papers is how Peirce’s semiotics could help to fulfill a conceptual gap in psychoanalysis in relation to phenomena that occur between what are called “symbolic equations” (representations lived as facts, by psychotic patients) and symbolization (the term used in psychoanalysis) as proper representation. Another article questions Jacques Lacan conception that the unconscious is structured like a language, suggesting that Peirce’s signs, particularly the icons and indices, would be more appropriate to think about the unconscious phenomena than the linguistics ones used by Lacan. The third paper gives a good example of how Peirce’s philosophic notions can be enlightening in the clinical area, as they are used to answer the criticism that the words could not be understood by a baby in a “mother-infant” treatment. The author says that when he speaks he is not only using symbolic signs, but also icons and indices, through facial expressions, attitude, tone of voice, etc., that can be transmitted to the babies. The last paper is more complex, as it attributes doubtful meanings to some of Peirce’s conceptions that need to be discussed.